Pengaruh Terpaan Iklan Instagram Ads @scarlett_whitening Terhadap Minat Beli Produk Scarlett Whitening - Putri, Adinda; Lubis, Fardiah Oktariani; Nurkinan, Nurkinan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The study entitled "The Effect of Instagram Ads Exposure @scarlett_whitening on Interest in Buying Scarlett Whitening Products" aims to determine and measure Instagram ad exposure @scarlett_whitening to the intention to buy Scarlett Whitening products. This study uses the uses and gratification theory, using quantitative methods with an explanatory approach. The population of this research is followers of the Instagram account @scarlett_whitening. The data collection method used is a questionnaire. Based on the normality test, simple linear regression test, hypothesis test (t), and test the coefficient of determination that exposure to Instagram ads @scarlett_whitening has a significant effect on the intention to buy Scarlett Whitening products.